Incretin‐based drugs and risk of lung cancer among individuals with type 2 diabetes. Issue 5 (11th March 2020) - Rouette, J.; Yin, H.; Yu, O. H. Y.; Bouganim, N.; Platt, R. W.; Azoulay, L.
Abstract: Aim: To assess whether dipeptidyl peptidase‐4 inhibitors and glucagon‐like peptide‐1 receptor agonists are associated with an increased lung cancer risk among individuals with type 2 diabetes. Methods: We conducted a population‐based cohort study using the UK Clinical Practice Research Datalink. We identified 130 340 individuals newly treated with antidiabetes drugs between January 2007 and March 2017, with follow‐up until March 2018. We used a time‐varying approach to model use of dipeptidyl peptidase‐4 inhibitors and glucagon‐like peptide‐1 receptor agonists compared with use of other second‐ or third‐line antidiabetes drugs. We used Cox proportional hazards models to estimate the adjusted hazard ratios, with 95% CIs, of incident lung cancer associated with use of dipeptidyl peptidase‐4 inhibitors and glucagon‐like peptide‐1 receptor agonists, separately, by cumulative duration of use, and by time since initiation. Results: A total of 790 individuals were newly diagnosed with lung cancer (median follow‐up 4.6 years, incidence rate 1.5/1000 person‐years, 95% CI 1.4–1.6). Compared with use of second‐/third‐line drugs, use of dipeptidyl peptidase‐4 inhibitors and glucagon‐like peptide‐1 receptor agonists was not associated with an increased lung cancer risk (hazard ratio 1.07, 95% CI 0.87–1.32, and hazard ratio 1.02, 95% CI 0.68–1.54, respectively). There was no evidence of duration–response relationships. Conclusions: In individuals with type 2 diabetes, use of incretin‐based drugs was not associated with increased lung cancer risk. What's new?: Although incretin‐based drugs improve glycaemic levels among individuals with type 2 diabetes, the role of these drugs in cancer incidence is currently debated, particularly in lung cancer where the limited evidence to date warrants further investigation. Compared with use of other second‐/third‐line drugs, incretin‐based drugs were not associated with increased lung cancer risk. The association remained nonsignificant in subgroups of individual drug classes and molecules, and in subgroups of individuals with long‐term use and smoking history. This study suggests that incretin‐based drugs do not increase lung cancer risk in individuals with type 2 diabetes in the first decade of use.